(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: We aimed to evaluate the potential of Ampiang-Dadih (AD), a combination of Indonesian traditional fermented buffalo milk (Dadih) and black glutinous rice flakes (Ampiang) as an anti-hypercholesterolemic agent and to prevent liver-cell degeneration using a rat model. Materials and Methods: A mixture of black glutinous rice powder (0.3 gm/gm feed) and fermented buffalo milk (3.74/200 gm BW) was prepared to obtain AD. Fifteen adult male Sprague Dawley rats were divided into three groups of five animals each: (A) negative control group (distilled water; 5 weeks), (B) hypercholesterolemia group (1% cholesterol per feed; 5 weeks), and (C) preventive AD group (1% cholesterol and AD; 5 weeks). The blood lipid profiles were measured at weeks 2, 4, and 5. The liver enzyme activity, cholesterol level, and histology were observed at the end of week 5. Results: AD administration simultaneously with cholesterol in Group C significantly prevented an increase in total plasma cholesterol and low-density lipoprotein levels compared to Group B. Alanine transaminase and aspartate transaminase were maintained at normal levels in Group C. Furthermore, the levels of liver cholesterol and liver cell degeneration in Group C were also maintained because of AD administration compared to that in Group B. Conclusion: This study demonstrated that AD has the potential to be developed as a functional food for hypercholesterolemia prevention. Adv. Vet. Anim. Res., 11(2): 275-283, June 2024 http://doi.org/10.5455/javar.2024.k773